(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Tverezovska N. T., Kasatkin D. YU. General didactic and specific principles of work in computer-oriented learning environments. The features of student learning in computer-oriented learning environments are defined; general didaktic and specific principles of operation, the characteristics inherent in computer-oriented learning environments are given.